A biogeography-based management for Mytilus chilensis: The genetic hodgepodge of Los Lagos versus the pristine hybrid zone of the Magellanic ecotone - Diaz-Puente, Borja; Pita, Alfonso; Uribe Paredes, Juan Carlos; Cuellar-Pinzon, Jose; Guinez, Ricardo; Presa, Pablo (My University, 2020)
This study was intended to identify mussel species from the Magellanic ecotone, quantifying interspecific hybridization within Mytilus and depicting the genetic architecture of Mytilus chilensis in its South Pacific range. The analysis comprises the sub-Antarctic Magallanes Province as a rich ecotone of climates, ecosystems and admixed faunas embedded among the biogeographic regions of the Pacific, the Atlantic, and Antarctica. Highly conserved molecular sequences within species were used to identify species, and polymorphic microsatellites were used to calculate the genetic architecture of M. chilensis. The absence of the invasive species Mytilus galloprovincialis from the M. chilensis range clarifies previous doubts on its expansion southward from the Arauco Gulf. The ubiquitous presence of the typical Glu-5 '-Me-15/16 PAP allele of Mytilus trossulus in the Northern Hemisphere might come from hull biofouling, but rather it seems to be an ancient polymorphism conserved in M. chilensis as occurs in blue mussels from other regions of the Southern Hemisphere. There is a very limited connectivity (F-ST = 0.167) between two latitudinal gene pools of M. chilensis that are highly divergent in composition, architecture, and ecological relevance. Fifty years of aquaculture enhancement in Los Lagos explains its high diversity and genetic heterogeneity among patches, so its mussel management should seek a balance between exploitation and environmental sustainability. The Magellanic ecotone bears a pristine M. chilensis x Mytilus edulis platensis hybrid zone around the Southern Cone, larger (450 km) than previously thought. Such a hybrid zone permeates one of the last remaining wilderness areas in the world (Cape Horn Biosphere Reserve) and is a natural laboratory for addressing introgression, hybridization, and evolution of Mytilus spp. genomes in their last southern frontier.
Keywords: alien species; aquaculture; blue mussels; invertebrates; reservoir; special area of conservation